2015
DOI: 10.15761/docr.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge, attitude and practice (KAP) among prison inmates of Ambala District, Haryana (India)

Abstract: Aim:The study was to assess the oral health knowledge, attitude and practice among prison inmates of Ambala district (Haryana) India. Materials and method:It was a cross sectional study conducted on 570 prisoners after meeting the eligibility criteria. A 23 item closed ended structured questionnaire was used to assess the oral health related knowledge, attitude and practice among prison inmates.Results: the results show that oral health knowledge was poor among prisoner as 51% of the subjects did not know abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…A drastic increase in knowledge regarding the same was seen at the end of six months to 99.2% in the present study. Only 46.3% knew about dental caries, and 62.1% did not know the meaning of gum bleeding in this study, which was similar to the findings of Digra et al, 2015. There was an increase in knowledge after the oral health education programme, and at the end of six months, it was observed that 82.9% of the inmates knew about dental caries, and 75.4% knew the correct meaning of gum bleeding. Further, 72.9% of the subjects believed that smoking is injurious to health, and 70.4% subjects knew that it could cause cancer and may be attributed to the warning sign over the tobacco products.…”
Section: Discussionsupporting
confidence: 85%
“…A drastic increase in knowledge regarding the same was seen at the end of six months to 99.2% in the present study. Only 46.3% knew about dental caries, and 62.1% did not know the meaning of gum bleeding in this study, which was similar to the findings of Digra et al, 2015. There was an increase in knowledge after the oral health education programme, and at the end of six months, it was observed that 82.9% of the inmates knew about dental caries, and 75.4% knew the correct meaning of gum bleeding. Further, 72.9% of the subjects believed that smoking is injurious to health, and 70.4% subjects knew that it could cause cancer and may be attributed to the warning sign over the tobacco products.…”
Section: Discussionsupporting
confidence: 85%
“…Considering all the above and regarding the similar evidence from different countries including India [20][21][22][23], Saudi Arabia [24,25], Egypt [26], Turkey [27], Pakistan [17], China [16,18] have indicated that in spite of differences among the level of knowledge, attitude and practice in the area of oral and dental health and despite the vast variety in the mechanism, method and rate of oral health information seeking behavior, effective interventions especially educational ones need to be designed to improve the oral health KAP. So it is recommended to design applied educational interventions using the potentiality of the internet and social media to increase the familiarity of the community with the new methods of seeking information and the pros and cons of applying the internet for this purpose.…”
Section: Discussionmentioning
confidence: 72%
“…A semi-structured interview guide developed from previous oral healthcare-related studies [ 17 20 ] that examined the knowledge, attitudes, practices, and confidence of various populations regarding oral healthcare was used to conduct face-to-face interviews with caregivers and administrators at nursing homes in San Antonio. Two different survey instruments were used for interviewing the caregivers and administrators.…”
Section: Methodsmentioning
confidence: 99%